Serum Lipid Profile in Hypothyroid Patients in Nepal - Aryal, Sudip; Joshi, A (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Hypothyroidism is non-curable common endocrine disorder in which the thyroid gland is unable to produce enough thyroid hormone. Present with a number of symptoms, Having a low level of thyroid hormone affects our whole body. Untreated hypothyroidism can be the cause of raised cholesterol levels. Many study have shown association between hypothyroidism and lipid profile. In this study, we evaluate the mean lipid profile status in subclinical hypothyroidism and hypothyroid patients. MATERIAL AND METHODS: A hospital based retrospective study done from the record card maintained in Alka Hospital, Jawalakhel. Total number of participants were 215. Out of which 73 had overt hypothyroidism, 92 had subclinical hypothyroidism and 50 were taken as control. SPSS version 20 was used for data analysis. RESULTS: The level of LDL, TG and TC was significantly higher in case of overt hypothyroidism as compared to control group, but no significant difference was found in subclinical hypothyroidism and control group. TG level was significantly lower in subclinical hypothyroidism cases. CONCLUSION: Elevated HDL, LDL & TC is seen in overt hypothyroid patients. It is important to screen for lipid profile in hypothyroid patients. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12065 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 33-36